Uterine prolapse and related factors in beef cow at the Besuki Animal Health Center, Situbondo regency, East Java, Indonesia - Kevin Mardotillah; Suzanita Utama; Erma Safitri; Herry Agoes Hermadi; Sri Pantja Madyawati; Djoko Legowo; Abdullah Hasib (Universitas Airlangga, 2024)
This study aims to determine the factors related to uterine prolapse in beef cow in the Besuki Animal Health Center working area in Situbondo regency. The sample consisted of 100 cows that calved in 2020-2022, whose data was obtained from the Department of Animal Husbandry of Situbondo regency, East Java, Indonesia. Determination of the months of the rainy and dry season was obtained from the Meteorological, Climatological and Geophysical Agency, Juanda Class I Meteorological Station. Other data regarding breed, age, parity of cow and dystocia incidence in cow was obtained by conducting interviews with farmers followed by confirmation with inseminator records, and direct observation of the housing system. The collected data were cross-tabulated and analyzed using Chi-square analysis to determine possible factors causing uterine prolapse. The results showed that the incidence of uterine prolapse in beef cow in the working area was 35% (35/100). The factors of housing, age, parity, and incidence of dystocia were significantly related (p <0.05) to the incidence of uterine prolapse, while breed and season did not have a significant influence (p > 0.05). It could be concluded that the age and parity of the cow at the time of calving, the practice of housing cow, and the incidence of dystocia were related to the incidence of uterine prolapse in cows in the Besuki Animal Health Center operational area.